(3LdGA GdbdhHs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s ((3EHQGgje Hf eUWais)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd Gddjd hGdfgGQ NdaI CeG HYO abO Qhi eSde aj UMjMg Yf Jeje GdOGQjCf CcJH QSGdI aj gPG GdTCf cJHJ gPg GdQSdI djchf UbdG ddUOhQ hLdGA ddbdhHs
(3BNQgG (B:s
(3GdLfI GdJj gj OGQ GdSdGe hLhGQ GdQMef dG jONdg EdG ef Sde ef GdbHhQ hNdU ef GdPfhH hdh HONhd GdfGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 176s
(3cTa GdXfhf(B: 1 / 592s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs